Genetic algorithm for intrusion detection system - BAYDOĞMUŞ, GÖZDE KARATAŞ (IEEE, 345 E 47th St, New York, Ny 10017 USA, 2016)
Intrusion detection systems are systems that prevent or slow the serving of different types of server data traffic caused by intensive use of networks that spread by internet. Particularly in recent years, because of increase in data density, need for these systems is increased thus different detection algorithms are being developed. In this study, information about the different detection algorithms using genetic algorithm, which are made of IDS algorithms is given and literature search's been made.
Genetik Algoritma ile Saldırı Tespit Sistemi
Keywords: intrusion detection systems; genetic algorithm